Study for re-ASR behaviour of recycled concrete using ASR generated concrete and considering countermeasure technology - Takeshi Iyoda; Nobuhiro Matsuda (Acta Polytechnica CTU Proceedings)
It is predicted that the concrete volume to be discarded will increase due to the renewal of the concrete structures and the increase in the returned concrete from construction site. The use of this concrete block as recycled aggregate is very important in terms of sustainability. However, recycled aggregate concrete is difficult to use due to large problems such as drying shrinkage and freeze-thaw action. On the other hand, the aggregate used for the raw concrete is often unknown, suggesting the danger of ASR. There is no previous research about what kind of danger is caused when an aggregate having an ASR risk is used as a recycled aggregate. Therefore, in this study, recycled aggregate was made from raw concrete where ASR occurred, after that recycled concrete was manufactured using this aggregate. After this, ASR tests were conducted again for the recycled concrete. In addition, we examined whether recycled concrete using aggregates with properties improved by using the previously reported carbonation technique could be an ASR countermeasure technology. As a result, it was found that the recycled concrete using the ASR-generated raw concrete as aggregate can suppress ASR by using recurring ASR aggregate treated by carbonation technology.